2014
DOI: 10.1016/j.autneu.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and weight status on cardiac autonomic control in healthy children: A review

Abstract: Heart rate variability (HRV) analyses can provide a non-invasive evaluation of cardiac autonomic activity. How autonomic control normally develops in childhood and how this is affected by obesity remain incompletely understood. In this review we examine the evidence that childhood age and weight status influence autonomic control of the heart as assessed using HRV. Electronic databases (Pubmed, EMBASE and Cochrane Library) were searched for studies examining HRV in healthy children from birth to 18 years who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 63 publications
3
60
0
3
Order By: Relevance
“…Breathing patterns influence cardiovascular response (131, 139) with decreased heart rate variability in the neonate attributable in part to increased sympathetic activity and/or decreased parasympathetic activity with gradually increasing parasympathetic activity over the first year of life (140142). Infants normally spend about 70% of a 24 h period asleep, and those who subsequently succumb to SIDS demonstrate a decreased heart rate variability due to increased sympathetic activity and/or decreased parasympathetic activity in all sleep phases (active/quiet sleep) (129, 140).…”
Section: Introductionmentioning
confidence: 99%
“…Breathing patterns influence cardiovascular response (131, 139) with decreased heart rate variability in the neonate attributable in part to increased sympathetic activity and/or decreased parasympathetic activity with gradually increasing parasympathetic activity over the first year of life (140142). Infants normally spend about 70% of a 24 h period asleep, and those who subsequently succumb to SIDS demonstrate a decreased heart rate variability due to increased sympathetic activity and/or decreased parasympathetic activity in all sleep phases (active/quiet sleep) (129, 140).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was demonstrated that children with obesity may also display a similar imbalance between the two main branches of the ANS, the sympathetic (SNS) and parasympathetic nervous systems (PNS) [8]. This difference has been most often found to be an increase in SNS function, and a decrease in PNS function [8].…”
Section: Introductionmentioning
confidence: 99%
“…This difference has been most often found to be an increase in SNS function, and a decrease in PNS function [8]. In this way, childhood obesity is associated with cardiac autonomic dysfunction well before the traditional high-risk age for cardiovascular disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that diabetic children present HRV alterations characterized by reduction in overall variability and parasympathetic activity [10–16], however, these studies do not consider factors that influence the autonomic changes such as sex [17], age [18], ethnicity [19], body fat percentage [20] and casual blood glucose [15]. …”
Section: Introductionmentioning
confidence: 99%